Calibration of a whole-body counter system for dose assessment in emergency situations - Papadopoulou, Konstantina; Nikolakis-Plytzanopoulos, Antonios; Salpadimos, Nikolaos; Kolovou, Maria; Karfopoulos, Konstantinos; Potiriadis, Constantinos (HNPS Advances in Nuclear Physics, 2025)
Nuclear-propelled vessels (e.g. ships and submarines) are often stationed in the Greek port of Souda. To this end, a hypothetical release from a nuclear-powered submarine was produced and studied, using the decision-support system JRODOS. The study focused on determining the radiological risk to workers of the port. It was found that the internal contamination due to inhalation contributed more than 95% of the total effective dose, which was calculated as 175 mSv, assuming an 8-hour shift. Hence, the present study focused on internal dosimetry, by utilizing a Whole-Body Counter setup. The Whole-Body Counter (WBC) setup of Greek Atomic Energy Commission was calibrated experimentally and via Monte Carlo (MC). The RMC-II phantom was used to calibrate the system experimentally. The Monte Carlo code PENELOPE was applied to model and calibrate the system. The MC efficiency calibration was within 6% mean relative bias compared to the experimental. The Minimum Detectable Activity (MDA) of the setup was calculated for every radionuclide considered from the hypothetical accident scenario, and detailed internal dose assessment was performed for the representative worker. The results were compared with the ones obtained by JRODOS.